In vitro biomechanical properties of porcine perineal tissues to better understand human perineal tears during delivery - Marine Lallemant; Tiguida Kadiakhe; Jerôme Chambert; Arnaud Lejeune; Rajeev Ramanah; Nicolas Mottet; Emmanuelle Jacquet (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Data concerning the mechanical properties of the perineum during delivery are very limited. In vivo experiments raise ethical issues. The aim of the study was to describe some of the biomechanical properties of each perineal tissue layer collected from sows in order to better understand perineal tears during childbirth. Material and methods Samples of each perineal tissue layer were obtained from the skin, the vagina, the external anal sphincter (EAS), the internal anal sphincter (IAS), and the anal mucosa of fresh dead sows. They were tested in quasi‐static uniaxial tension using the testing machine Mach‐1®. Tests were performed at a displacement velocity of 0.1 mm·s−1. Stress–strain curves of each perineal tissue layer before the first damage for each sow were obtained and modeled using a hyperelastic Yeoh model described by three coefficients: C1, C2, and C3. Pearson correlation coefficients were calculated to measure the correlation between the C1 hyperelastic coefficient and the duration between the first microfailure and the complete rupture for each perineal tissue layer. Pearson correlation was computed between C1 and the number of microfailures before complete rupture for each tissue. Results Ten samples of each perineal tissue layer were analyzed. Mean values of C1 and corresponding standard deviations were 46 ± 15, 165 ± 60, 27 ± 10, 19 ± 13, 145 ± 28 kPa for the perineal skin, the vagina, the EAS, the IAS, and the anal mucosa, respectively. According to this same sample order, the first microfailure in the population of 10 sows appeared at an average of 54%, 27%, 70%, 131%, and 22% of strain. A correlation was found between C1 hyperelastic coefficient and the duration between the first microfailure and the complete rupture (r = 0.7, p = 0.02) or the number of microfailures before complete rupture only for the vagina (r = 0.7, p = 0.02). Conclusions In this population of fresh dead sow's perineum, the vagina and the anal mucosa were the stiffest tissues. The IAS and EAS were more extensible and less stiff. A significantly positive correlation was found between C1 and the duration between the first microfailure and the complete rupture of the vagina, and the duration between the first microfailure and the complete rupture of the vagina.